KEBIJAKAN PEMERINTAH DAERAH DALAM ANGGARAN SEKTOR PENDIDIKAN - Yudrik JahJa (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2007)
Based on the 1945 Constitution, the government is obliged to provide annual budget for conducting national education at amount of 20% from APBN and APBD. The implementation of this regulation is controversial and has not been done fully. This article discusses the provision of education budget by reviewing the rule of region in contributing there local budget for education development in their regions. It is concluded that in general the contribution of each region is still low. The article suggests that the local governments should improve their policy in allocating their budget for education development to improve the quality as well as the quantity of education in their own regions.